2001
DOI: 10.1089/104303401750270968
|View full text |Cite
|
Sign up to set email alerts
|

Systemically Expressed Soluble Tie2 Inhibits Intraocular Neovascularization

Abstract: Retinal and choroidal neovascularization are the most frequent causes of severe and progressive vision loss. Studies have demonstrated that Tie2, an endothelial-specific receptor tyrosine kinase, plays a key role in angiogenesis. In this study, we determined whether adenovirus-mediated gene delivery of extracellular domain of the Tie2 receptor (ExTek) could inhibit experimental retinal and choroidal neovascularization. Immunofluorescence histochemistry with a monoclonal antibody to human Tie2 showed that Tie2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 41 publications
3
36
0
1
Order By: Relevance
“…54 Furthermore, inhibition of the Tie2 receptor with adenovirus-mediated gene delivery also attenuates angiogenesis in mouse models of ROP and choroidal neovascularization. 55 The findings of the present study support an angiogenic role for Ang2 and Tie2 as both were increased with ROP in the setting of elevated VEGF, whereas Ang1 mRNA remained unchanged. In ROP, the stimulus for up-regulation of VEGF is tissue hypoxia, 7,25,48 which may also be the case for Ang2 and Tie2 as initially observed in rat glioma cells and BRECs.…”
Section: Discussionsupporting
confidence: 80%
“…54 Furthermore, inhibition of the Tie2 receptor with adenovirus-mediated gene delivery also attenuates angiogenesis in mouse models of ROP and choroidal neovascularization. 55 The findings of the present study support an angiogenic role for Ang2 and Tie2 as both were increased with ROP in the setting of elevated VEGF, whereas Ang1 mRNA remained unchanged. In ROP, the stimulus for up-regulation of VEGF is tissue hypoxia, 7,25,48 which may also be the case for Ang2 and Tie2 as initially observed in rat glioma cells and BRECs.…”
Section: Discussionsupporting
confidence: 80%
“…However, emerging evidence suggests that additional signaling of ANG-1 and ANG-2 through integrin receptors may be important in their diverse contribution toward tumor growth. The existence of various ligands (ANG-1, ANG-2, and ANG-4), their isoforms [four ANG-1 isoforms (31) and two ANG-2 isoforms (125)], and soluble forms of TIE-1 and TIE-2 receptors (126, 127) and TIE-2/TIE-1 heterodimerization in modulating receptivity (73) and differential induction of both receptors and ligands (119,128,129) compounded the difficulty of precise definition of the role of the ANGs during angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The mice showed no side effects related to the treatment, nor was there evidence of toxicity within the retinal tissues. Previous studies have employed either an im injection of an adenovirus expressing the extracellular domain of the Tek/Tie 2 receptor (Hangai et al, 2001) or an intraocular injection of a soluble Tie-2 receptor/Fc fusion protein similar to the one used in the present study. Results from these studies have demonstrated a similar although significantly lower degree of inhibition (47% and 23%, respectively) of retinal neovascularization in the same mouse model.…”
Section: Discussionmentioning
confidence: 99%